Characteristics and factors associated with nosocomial pneumonia among patients undergoing continuous renal replacement therapy (CRRT): A case–control study. (March 2018) - Zuo, Manhua; Tang, Jun; Xiang, Miaomiao; Long, Qing; Dai, Jianping; Hu, Xiuying
Highlights: The characteristics of the pathogens and risk factors for nosocomial pneumonia in patients on continuous renal replacement therapy (CRRT) were investigated and demonstrated through a retrospective case–control study. A large sample of 1160 cases was collected from the electronic medical archives and paper case records of a tertiary-care hospital. Univariate and multivariate logistic regression analysis revealed the factors influencing nosocomial pneumonia in CRRT patients. Understanding the factors influencing nosocomial pneumonia in patients receiving CRRT would be beneficial to the care and treatment provided by dialysis nurses and nephrologists. Abstract: Objectives: Continuous renal replacement therapy (CRRT) is a specialized type of dialysis. However, the characteristics and factors associated with nosocomial pneumonia in patients undergoing CRRT have received little attention to date. Therefore, this study investigated the characteristics of and factors contributing to nosocomial pneumonia in patients receiving CRRT. Methods: The clinical data of 1160 patients undergoing CRRT during the period January 2008 to December 2015 were analyzed retrospectively. Of these 1160 cases, 145 (12.5%) were included in the nosocomial pneumonia group, while 1015 were included in the control group. Results: The primary pathogen in the 145 cases of nosocomial pneumonia in the CRRT patients was Staphylococcus aureus (58.57%); the morbidity rate was 12.5%. Multivariate logistic regression analysis revealed that age (odds ratio (OR) 2.209), initial curative time (OR 1.960), underlying diseases (OR 1.820), consciousness disorder (OR 1.616), organ failure (OR 2.154), the Acute Physiology and Chronic Health Evaluation II score (APACHE II) (OR 1.186), and the Charlson Comorbidity Index score (CCI) (OR 1.278) were risk factors for nosocomial pneumonia (all p < 0.05). Conversely, the serum white blood cell count (OR 0.585), albumin (OR 0.673), and hemoglobin (OR 0.712) levels were protective factors (all p < 0.05). Conclusions: Results from this study indicate that by modifying risk factors, such as providing adequate nutrition, earlier treatment of underlying diseases, and controlling organ failure, the risks associated with nosocomial pneumonia may be reduced.